Morphological alterations on human radicular dentin after exposure to different fruit juice drinks - Zandim-Barcelos, Daniela Leal [UNESP]; Martins, Cínthia Oliveira [UNESP]; Cavassim, Rodrigo [UNESP]; Rossa Júnior, Carlos [UNESP]; Abi-Rached, Ricardo Samih Georges [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (FapUNIFESP (SciELO), 2011)
Purpose: This in vitro study aimed to evaluate the effect of different fruit juice drinks available in the Brazilian market on smear layer removal and dentinal tubules opening, as well as to verify the effect of toothbrushing subsequently to the juices exposure. Methods: Dentin specimens were prepared and randomly distributed into the control group (distilled water) and twelve types of fruit juice drinks (cashew, orange, mandarin, apple, passion fruit, guava, strawberry, grape, mango, pear, peach, pineapple). The following treatments were applied: immersion or immersion + brushing. After preparation for SEM, photomicrographs were assessed using an index of smear layer removal. Results: No significant differences regarding smear layer removal and dentinal tubules exposure could be observed between the groups after both treatments (Kruskal-Wallis, post-hoc paired comparisons, P>0.05). The control solution and the fruit juice drinks were not able to remove smear layer and to open dentinal tubules. Significant difference between the applied treatments was detected only for the mango juice group (Mann-Whitney, P<0.05). Conclusion: Under the experimental conditions, the different fruit juice drinks did not promote significant alterations on human radicular dentin morphology regardless of the subsequent application of brushing procedures. Copyright: © 2011 Zandim et al.
Keywords: Acids; Dentin; Dentin sensitivity; Diet; Smear layer